2018
DOI: 10.24136/eq.2018.036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of business support organizations on innovation activity in manufacturing companies in the Masovian Voivodeship in Poland

Abstract: Research background: The first business support organizations (BSO) appeared in Poland in the 90s of the last century. They were transferred from Western Europe and the United States, where they provided system solutions and played an important role in stimulating innovation activity. However, the latter regions are economically developed, while Poland is playing catch-up. The important question is whether business support organizations will significantly increase the innovative potential of  Polish enterprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Measures undertaken for the qualitative and quantitative development of resources through cooperation with other companies do not affect the possibilities of innovative development (Corral de Zubielqui et al, 2018). Innovation research often leads to establishing factors, patterns and trends in the development of enterprises or their tendency to innovate, including regional and sectoral analyses based on entrepreneurial surveys studies (Spitsin et al, 2018, Zygmunt, 2017, Gorączkowska, 2018. Cieślik and Michałek (2018) indicate positive relations between innovations and business efficiency.…”
Section: Methodology and Theorymentioning
confidence: 99%
“…Measures undertaken for the qualitative and quantitative development of resources through cooperation with other companies do not affect the possibilities of innovative development (Corral de Zubielqui et al, 2018). Innovation research often leads to establishing factors, patterns and trends in the development of enterprises or their tendency to innovate, including regional and sectoral analyses based on entrepreneurial surveys studies (Spitsin et al, 2018, Zygmunt, 2017, Gorączkowska, 2018. Cieślik and Michałek (2018) indicate positive relations between innovations and business efficiency.…”
Section: Methodology and Theorymentioning
confidence: 99%
“…The roles of the technology, industrial and scientific parks in the country's innovative development and perspectives of their creation and functioning are studied in works of such native and foreign scientists as I. Dumanska [7] (principles of financing of the activity of industrial parks), J. Goraczovska [8] (technology parks influence on the innovation activity of enterprises), V. Halasiuk [9] (perspectives of creation of industrial parks in Ukraine), Yu. Kozak, I. Ukhanova [10,11] (the role of technology parks in real economy and their development in the system of providing of innovation policy), A. Mazur, S. Pustovoit [12] (development of technology parks in Ukraine), etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is observed that—depending on specific conditions—all these feedbacks can be both positive and negative, and their effects overlap, which creates a complex pattern of industrial processing in Poland. The innovative activity of enterprises also depends on many other factors such as the national and international environment [ 14 , 15 , 16 ], management system [ 17 ], business support organizations [ 18 , 19 ], intellectual assets [ 20 ], sectoral patterns of cooperation and technology level [ 21 ], for which the ceteris paribus assumption was made. It can also affect other economic variables such as total factor productivity [ 22 ], the level of firm productivity [ 23 ], and anti-crisis reputational sustainability [ 24 ].…”
Section: Introductionmentioning
confidence: 99%